2019
DOI: 10.1002/yea.3385
|View full text |Cite
|
Sign up to set email alerts
|

Vitis species, vintage, and alcoholic fermentation do not drive population structure in Starmerella bacillaris (synonym Candida zemplinina) species

Abstract: The yeast species Starmerella bacillaris (synonym Candida zemplinina) is widely associated with oenological ecosystems and is frequently isolated from grape and grape must. Previous work showed that the genetic diversity of this species is high in wine environments and it is shaped by geographic location. Most analysed C. zemplinina strains, however, have been isolated from Vitis vinifera, disregarding the existence of other worldwide-distributed Vitis species used in winemaking. In this work, we address the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 45 publications
2
7
0
Order By: Relevance
“…The chromosome alignments analyzed showed a general synteny between both genomes, with a high number of single nucleotide polymorphisms (SNPs) (i.e., 33,771 variants among 1146 putative genes) [29]. These observations highlight the large potential biodiversity among wild isolates of S. bacillaris, as has been reported by other authors [37][38][39].…”
Section: S Bacillaris Genomesupporting
confidence: 74%
See 4 more Smart Citations
“…The chromosome alignments analyzed showed a general synteny between both genomes, with a high number of single nucleotide polymorphisms (SNPs) (i.e., 33,771 variants among 1146 putative genes) [29]. These observations highlight the large potential biodiversity among wild isolates of S. bacillaris, as has been reported by other authors [37][38][39].…”
Section: S Bacillaris Genomesupporting
confidence: 74%
“…This study also showed that Argentinian S. bacillaris populations are more differentiated from European populations than S. bacillaris populations within Europe [37]. In addition, no evidence of genetic differentiation based on the Vitis species or vintages, nor an evolving S. bacillaris population during alcoholic fermentation was found [37]. Overall, no genetic signature of S. bacillaris strains was found associated with different vintages, Vitis species, vineyards, and/or wineries, indicating that winemaking-related factors (i.e., Vitis species, vintage, alcoholic fermentation, and/or wineries) do not impact S. bacillaris population structure [37,38].…”
Section: S Bacillaris Ecologysupporting
confidence: 62%
See 3 more Smart Citations